GRP78 Interacting Partner Bag5 Responds to ER Stress and Protects Cardiomyocytes From ER Stress‐Induced Apoptosis. Issue 8 (21st January 2016) - Gupta, Manish K.; Tahrir, Farzaneh G.; Knezevic, Tijana; White, Martyn K.; Gordon, Jennifer; Cheung, Joseph Y.; Khalili, Kamel; Feldman, Arthur M.
ABSTRACT: Bag5 is a member of the BAG family of molecular chaperone regulators and is unusual in that it consists of five BAG domains, which function as modulators of chaperone activity. Bag family proteins play a key role in cellular as well as in cardiac function and their differential expression is reported in heart failure. In this study, we examined the importance of a Bag family member protein, Bag5, in cardiomyocytes during endoplasmic reticulum (ER) stress. We found that expression of Bag5 in cardiomyocytes is significantly increased with the induction of ER stress in a time dependent manner. We have taken gain‐in and loss‐of functional approaches to characterize Bag5 protein function in cardiomyocytes. Adenoviral mediated expression of Bag5 significantly decreased cell death as well as improved cellular viability in ER stress. Along with this, ER stress‐induced CHOP protein expression is significantly decreased in cells that overexpress Bag5. Conversely, we found that siRNA‐mediated knockdown of Bag5 caused cell death, increased cytotoxicity, and decreased cellular viability in cardiomyocytes. Mechanistically, we found that Bag5 protein expression is significantly increased in the ER during ER stress and that this in turn modulates GRP78 protein stability and reduces ER stress. This study suggests that Bag5 is an important regulator of ER function and so could be exploited as a tool to improve cardiomyocyte function under stress conditions. J. Cell. Biochem. 117: 1813–1821, 2016. © 2016 Wiley Periodicals, Inc.